2019
DOI: 10.1155/2019/3745735
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Associated with Thrombotic Disease Comparison of Two Territories: Myocardial Infarction and Ischemic Stroke

Abstract: Background and Purpose The thrombin-activatable fibrinolysis inhibitor (TAFI) is an important inhibitor of fibrinolysis and plays a critical role in the pathogenesis of arterial thrombosis; genetic polymorphisms of the TAFI gene affect its activity and increase the risk of thrombosis. Moreover, studies in young patients are still scarce. The aim was to examine the contribution of the Thr325Ile and Ala147Thr polymorphisms with ST acute myocardial infarction (STEMI) or idiopathic ischemic stroke (IIS) in the you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…2019 [124] Thr/Ile325 polymorphism in the CPB2 gene was associated with an increased risk for STEMI (N = 244), but not for IIS (N = 250). Genotype and allele distribution were similar in IIS patients and controls (N = 244).…”
Section: Arterial Thrombosis and Coronary Artery Disease (Cad)mentioning
confidence: 97%
See 1 more Smart Citation
“…2019 [124] Thr/Ile325 polymorphism in the CPB2 gene was associated with an increased risk for STEMI (N = 244), but not for IIS (N = 250). Genotype and allele distribution were similar in IIS patients and controls (N = 244).…”
Section: Arterial Thrombosis and Coronary Artery Disease (Cad)mentioning
confidence: 97%
“…Rattanawan and co-workers selected a total of 327 patients that were scheduled for an elective coronary angiography and found that the +1040C/T polymorphism was not associated with more severe coronary stenosis [ 125 ]. Another study reported that the Thr/Ile325 polymorphism was associated with an increased risk for STEMI but not for idiopathic ischemic stroke in young individuals [ 124 ]. A meta-analysis conducted by Shi and colleagues showed that the Thr/Ile325 variant had no significant influence on the susceptibility for cardiovascular diseases (CVD).…”
Section: Plasma Procpu Concentration and Procpu Polymorphisms As Rmentioning
confidence: 99%
“…Even though several studies could provide a link between TAFI gene SNPs and cerebral venous thrombosis [ 69 ], venous thromboembolic disease [ 70 , 71 ], myocardial infarction [ 72 , 73 ], stroke [ 74 ], and coronary heart disease [ 75 , 76 ], a clear link remains controversial as it could not be established by many other studies [ 77 , 78 , 79 , 80 , 81 , 82 ]. Similarly, independent of the contribution from TAFI gene SNPs, ample evidence has been provided of a link between elevated TAFI levels and venous thromboembolic disease [ 83 , 84 ], deep vein thrombosis [ 85 ], stroke [ 82 , 86 , 87 ], and coronary heart disease [ 88 ].…”
Section: (Patho)physiological Role Of Tafimentioning
confidence: 99%
“…Apžvelgus į literatūros analizę įtrauktus tyrimus, išskirtos kelios tokių rizikos veiksnių grupės -tam tikrų genų (ADPIOQ, ESR2, TAFI, ACE, FII ir kt.) polimorfizmas [21,22,[24][25][26], krešėjimo faktorių kiekio ar aktyvumo pokyčiai [27,28], šeiminė hipercholesterolemija [29][30][31], telomerų ilgio pokyčiai [23].…”
Section: Autorius Metai šAlisunclassified
“…Literatūros apžvalgai iš viso atrinktos 25 publikacijos, kurios buvo suskirstytos į 3 grupes -4 tyrimai nustatantys bendrą rizikos veiksnių paplitimą tarp pacientų, MI patyrusių jauname amžiuje [9][10][11][12], 10 tyrimų, lyginančių rizikos veiksnių paplitimą tarp jaunų bei vyresnio amžiaus pacientų [6,7,[14][15][16][17][18][19][20][21] ir 11 tyrimų, tiriančių netradicinius jauname amžiuje persirgto MI rizikos veiksnius [23][24][25][26][27][28][29][30][31][32][33]. Mokslinių tyrimų atrankos procesas pateiktas schemoje (1 pav.…”
unclassified